Clinical evaluation of non-invasive prenatal screening in 32,394 pregnancies from Changzhi Maternal and Child Health Care Hospital of Shanxi China - Song, WenXia; Li, XiaoZe; Wang, LiHong; Yao, ZeRong; Ruan, FangYing; Hu, ZhiPeng (Journal of Medical Biochemistry, 2021)
Non-invasive prenatal screening (NIPS)was performed in 32,394 pregnancies, out of which results were available in 32,361 (99.9%) of them.Among the 32,361confirmed samples, 164 cases had positive results and 32197 cases had negative results. Of these positive cases, 116 cases were trisomy 21, 34 cases were trisomy 18 and 14 cases were trisomy 13. No false negative results were found in this cohort. The overall sensitivity and specificity were 100% and 99.91%, respectively. There was no significant difference in test performance between the 7,316 high-risk and 25,045 low-risk pregnancies，(sensitivity, 100% vs 100% (P >0.05); specificity, 99.96% vs 99.95% (P > 0.05)). Factors contributing to false-positive results included fetal CNVs, fetal mosaicism and typically producing Z scores between 3 and 4. Moreover, we analyze NIPT whole-genome sequencing to investigate the Single Nucleotide Polymorphisms (SNPs) associations with drug response or risk of disease. As compare to the 1000g East Asian genome data, the results reveal a significant difference in 7,285,418 SNPs variants of Shanxi pregnant women including 19，293 clinvar recorded variants and 7,266,125 non- clinvar recorded. Our findings showed that NIPS was an effective assay that may be applied as routine screening for fetal trisomies in the prenatal setting. In addition, this study also provides an accurate assessment of significant differencein 7,285,418 SNPs variants in Shanxi pregnant women that were previously unavailable to clinicians in Shanxi population.